If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + 2) = 2x + -18 Reorder the terms: -3(2 + 2x) = 2x + -18 (2 * -3 + 2x * -3) = 2x + -18 (-6 + -6x) = 2x + -18 Reorder the terms: -6 + -6x = -18 + 2x Solving -6 + -6x = -18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + -6x + -2x = -18 + 2x + -2x Combine like terms: -6x + -2x = -8x -6 + -8x = -18 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -8x = -18 + 0 -6 + -8x = -18 Add '6' to each side of the equation. -6 + 6 + -8x = -18 + 6 Combine like terms: -6 + 6 = 0 0 + -8x = -18 + 6 -8x = -18 + 6 Combine like terms: -18 + 6 = -12 -8x = -12 Divide each side by '-8'. x = 1.5 Simplifying x = 1.5
| 3y/-9=13=y/8 | | 2(2n+3)=9(9n+7)+6 | | 13-(-12x-20)=0 | | 6x+2(-5+6)=-36 | | 3x-1+x-19=180 | | 2a+2b=p | | 4n+9-6-3= | | X^3-6x^2=9x-54 | | 5x+7=7+x | | 12x-16=7x-3 | | 6y+4=6y-30 | | 0.23x=4.9+.3x | | (9x-5)(4x-5)= | | -3(-2x+2)=2x-18 | | 30x+(x^2+40x)+10x+35=180 | | 2p+3n=m | | x-(6/13)=4/13 | | X+4=3x-18 | | -3(2x-9)+2x=43 | | 7.50t=187.50 | | 18x+11=2(6x+2)+6x+7 | | 4.2+2.1x=6.3 | | 18÷2/3 | | 3n+2p=m | | 400/-9 | | 2x^2-9=3 | | 15/96 | | 12n^2+4n= | | 2x+10+4=-8 | | M^3y-27y= | | 8(4-2n)=-16n+16 | | 5(1+c)=6(2-c) |